How to measure SCRES? – the perspective of flexibility and redundancy in relationships with suppliers - Wieteska, Grażyna (Contemporary organisation and management. Challenges and trends, 2020)
The purpose of this paper is to present the proposal of a supply chain resilience (SCRES) measurement for the area of supplier relationship management. It is focused on two main SCRES elements, which are flexibility and redundancy. First, the article provides a multi-faceted analysis of publications that present systematic literature reviews on SCRES. Next, the results of several in-depth interviews on practices that increase resilience in relationships with suppliers are discussed. Finally, on the base of the conducted research, a measurement of flexibility and redundancy in relationships with suppliers is proposed. It covers four constructs which are: supplier flexibility, procurement flexibility, logistics flexibility and redundancy in supplier-buyer cooperation.